A Simple and Efficient Method to Fabricate Graphene 2D Nanomaterial into a thin Film to Serve as a Saturable a bsorber for Fiber Laser Application - I. Hammadi, Yousif; S. Mansour, Tahreer (International Journal of Engineering and Technology, 2018)
A passively pulsed fiber laser using saturable absorbers such as graphene has been increased dramatically in recent years. Up to now, researchers have been proposed many methods to fabricate graphene saturable absorber such as (evanescent coupling structure, electrochemical exfoliation, and mechanical exfoliation) for light pulse generation in a fiber laser. However, each of these methods has got some limitations which reduce the saturable absorber performance and restrict its range of applications. In this paper, we propose a simple but very efficient fabrication way of graphene saturable absorber by converting graphene Nano powder into a thin film using polyvinyl alcohol (PVA) as a host material. The fabricated film can then be easily sandwiched between two fiber pigtails and inserted inside the laser cavity to form the saturable absorber. when compared with other methods, this method is much preferable because it provides saturable absorber with combat structure, maximum interaction area, reasonable insertion loss, polarization insensitive, controllable concentration, and safe to handle. The fabricated graphene saturable absorber in this paper was characterized and found to have a uniform distribution of the graphene nanomaterial in the PVA and have a modulation depth of 6.1% which make it a very promising saturable absorber for ultra-fast fiber laser demonstration.Â Â